2012
DOI: 10.3325/cmj.2012.53.350
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and serum levels of adiponectin, vascular endothelial growth factor, and interleukin-6 in patients with rheumatoid arthritis

Abstract: AimTo investigate differences in body composition and body mass index (BMI) in patients with rheumatoid arthritis (RA) and their correlations with serum production of adiponectin, interleukin-6 (IL-6), and vascular endothelial growth factor (VEGF).MethodsThe study included 83 patients (age 53 ± 5 years) with RA treated with methotrexate. We determined their BMI, fat mass, and fat-free mass using bioimpedance analysis, and serum concentrations of adiponectin, VEGF, and IL-6 using immunoassay analysis.ResultsNor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…In our study, body mass, LBM, and BMI values were comparable between CTD and control groups. Similarly, other studies have not shown differences in fatfree mass (LBM) and fat mass between patients with rheumatoid arthritis and control groups if the groups have comparable BMI within the recommended range (<25 kg/m 2 ) [30,31]. But in our study, patients with CTD were characterized by higher water content, serum glucose, and triglyceride level when compared to healthy subjects.…”
Section: Journal Of Immunology Researchcontrasting
confidence: 42%
“…In our study, body mass, LBM, and BMI values were comparable between CTD and control groups. Similarly, other studies have not shown differences in fatfree mass (LBM) and fat mass between patients with rheumatoid arthritis and control groups if the groups have comparable BMI within the recommended range (<25 kg/m 2 ) [30,31]. But in our study, patients with CTD were characterized by higher water content, serum glucose, and triglyceride level when compared to healthy subjects.…”
Section: Journal Of Immunology Researchcontrasting
confidence: 42%
“…29 In addition to IL-6 concentrations increasing with disease severity, Il-6 concentrations are dependent on circadian variation and on body weight. 51 In 2000, the pharmacokinetics of the S-and R-enantiomers of verapamil were compared in 8 RA patients with 8 age-and sex-matched healthy volunteers. 10 Verapamil is a major substrate of CYP3A and a minor substrate of CYP1A2, CYP2B6, CYP2C9, and CYP2E1.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…One of the hormones secreted by adipocytes is adiponectin. It is one of the main regulators of carbohydrate and fat exchange, produced exclusively in fat tissue [Oranskiy et al, ] Obesity is associated with a decrease in circulating adiponectin [Kiortsis et al, ] but while weight loss has been shown to increase adiponectin, there are conflicting results [Christou et al, ]. This may be because there are several multimeric forms of adiponectin that circulate in humans [Waki et al, ] and rhesus monkeys [Bobbert et al, ].…”
Section: Introductionmentioning
confidence: 99%